Effects of 6-week squat, deadlift, or hip thrust training program on speed, power, agility, and strength in experienced lifters: A pilot study - Zweifel, M. B.; Vigotsky, A. D.; Contreras, B.; Njororai Simiyu, W. W. (Journal of Trainology, 2017)
Objectives: To compare the ergogenic effects of back squats, deadlifts, and hip thrusts. Design: Pilot randomized-controlled trial Methods: In order to determine the feasibility of such a large training study, a pilot study was carried out with 26 male and female participants (age = 22.15 ± 2.2 years; height = 180.17 ± 8.37 cm; body mass = 87.27 ± 15.72 kg). Subjects performed squats (n = 8), hip thrusts (n = 8), deadlifts (n = 6), or nothing (control) (n = 4) for three training sessions a week, for six weeks; thereafter, measures of sprinting performance, vertical jump, broad jump, strength, and change of direction were compared to baseline. Results: This pilot study was carried out successfully. Effect-sizes, medians, and interquartile ranges for all possible comparisons have been presented for power analyses. Conclusion: Although all of the studied interventions show promise, larger investigations are necessary in order to draw more definitive, applicable conclusions.